Antibacterial Activity of Silver Doped Titanate Nanowires on Ti Implants - Xu, Ziqiang; Li, Man; Li, Xia; Liu, Xiangmei; Ma, Fei; Wu, Shuilin; Yeung, K. W. K; Han, Yong; Chu, Paul K (ACS applied materials & interfaces, 2016)
A nanostructured film composed of one-dimensional titanate nanowires (TNWs) was employed as a carrier of Ag nanoparticles and chitosan (CS) to improve the surface antibacterial activity and biocompatibility of titanium implants. A TNWs film was produced on a Ti substrate by an alkali hydrothermal reaction and subsequently doped by Ag nanoparticles through an ultraviolet light chemical reduction. The CS nanofilm was deposited on the Ag nanoparticles through a spin-assisted layer by layer assembly method. The results disclosed that Ag nanoparticles were successfully carried by TNWs and homogeneously distributed on the entire surface. Moreover, a CS nanofilm was also successfully deposited on the Ag nanoparticles. Antibacterial tests showed that the samples modified with a higher initial concentration of AgNO3 solution exhibited better antibacterial activity, and that a CS nanofilm could further improve the antibacterial activity of the TNWs. Cell viability and ALP tests revealed that the release of Ag+ was detrimental for the growth, proliferation, and differentiation of MC3T3, and that CS could lower the negative effects of Ag gradually as the incubation time increased.